Menyelisik Financial Distress Melalui Lensa Model Grover - Fatmawati, Arsyi Dela; Sari, Shinta Permata (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Financial distress is a condition in which a company experiences financial difficulties that could potentially lead to bankruptcy if not handled properly. This study aims to analyze the effect of liquidity (Current Ratio, Quick Ratio, Cash Ratio), solvability (Debt to Total Equity Ratio), and profitability (Net Profit Margin) on Financial Distress in basic material companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024 using the Grover model. The data is secondary data obtained from company annual reports. From a population of 112 companies, 75 companies are selected as samples using purposive sampling. This study uses binary logistic regression with SPSS version 27 for hypothesis testing. The results show that the Current Ratio, Cash Ratio, and Net Profit Margin have effect on Financial Distress, while the Quick Ratio and Debt to Total Equity Ratio have no effect on Financial Distress. These findings emphasize the importance of liquidity and profitability management in minimizing the potential for Financial Distress in basic material sector companies.